2018
DOI: 10.1002/berj.3450
|View full text |Cite
|
Sign up to set email alerts
|

Turning heads: The impact of political reform on the professional role, identity and recruitment of head teachers in Wales

Abstract: This article considers the professional work, identity and recruitment of head teachers (HTs) in Wales. Drawing on the sociology of professions, the article illustrates how intensive educational policy reform post-2011 has restricted HTs' professional agency and re-orientated the head teacher role towards organisational professionalism. Drawing on semi-structured interviews (n=30) with both head and deputy head teachers, the article argues that issues with the recruitment and retention of HTs in Wales can, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 27 publications
1
43
0
6
Order By: Relevance
“…Managerial discourses can dominate school leaders' understandings of induction and mentoring (Sunde and Ulvik, 2014) and account for their highly positive views that differ from those of NQTs and the rest of the staff. We do not subscribe to criticism of leaders -their roles are excessively pressurized and in Wales recent research (Connolly et al, 2018) has identified problems in attracting individuals to the role.…”
Section: Discussionmentioning
confidence: 95%
“…Managerial discourses can dominate school leaders' understandings of induction and mentoring (Sunde and Ulvik, 2014) and account for their highly positive views that differ from those of NQTs and the rest of the staff. We do not subscribe to criticism of leaders -their roles are excessively pressurized and in Wales recent research (Connolly et al, 2018) has identified problems in attracting individuals to the role.…”
Section: Discussionmentioning
confidence: 95%
“…Esto es coherente con investigaciones recientes que señalan la construcción de nuevas identidades adaptativas como respuesta a las exigencias políticas (Connolly, Milton, Davies y Barrance, 2018). Y es que, la manera de resolver los conflictos de identidad no es a través de respuestas críticas, sino desarrollando identidades resilientes como un medio para mejorar el "yo", para hacerlo más útil en un espacio de demandas volátiles (Bailey, 2015).…”
Section: Reconstrucciones "Resilientes" De La Identidad Profesional Aunclassified
“…Since devolution in Wales, Welsh education policy has diverged from England and other parts of the UK, through WG reforms (see Power, 2016). As noted by Connolly et al (2018b), within the context of Wales, accountability measures have been introduced following narratives that reported declining educational quality (Dixon, 2016). The publication of school performance data as part of these measures have been justified by WG as a genuine concern with struggling schools, and a useful way of understanding how best to support struggling schools in Wales.…”
Section: Education Policy In Walesmentioning
confidence: 99%
“…As such, Welsh Government (WG) is currently working with others to develop future policy strategies for PRUs in Wales, which consider their current implementation of broader national education policy reforms (WG, 2017a). Recently it has been suggested that these broader reforms have contributed to a change in the professional role and identity of mainstream teachers and head teachers working within the Welsh education system (see Connolly et al, 2018a;Connolly et al, 2018b). These changes which are associated with a greater degree of external accountability measures and an increase in bureaucracy, have reframed teachers' and headteachers' professional practice.…”
Section: Introductionmentioning
confidence: 99%